2009
DOI: 10.1002/emmm.200900003
|View full text |Cite
|
Sign up to set email alerts
|

Induced chromosome deletions cause hypersociability and other features of Williams–Beuren syndrome in mice

Abstract: The neurodevelopmental disorder Williams–Beuren syndrome is caused by spontaneous ∼1.5 Mb deletions comprising 25 genes on human chromosome 7q11.23. To functionally dissect the deletion and identify dosage-sensitive genes, we created two half-deletions of the conserved syntenic region on mouse chromosome 5G2. Proximal deletion (PD) mice lack Gtf2i to Limk1, distal deletion (DD) mice lack Limk1 to Fkbp6, and the double heterozygotes (D/P) model the complete human deletion. Gene transcript levels in brain are ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
120
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(132 citation statements)
references
References 56 publications
11
120
0
1
Order By: Relevance
“…This dominantnegative explanation predicts that heterozygous mutants would have more severe consequences than a hemizygous Gtf2ird1 deletion. This does appear to be the case, as some of the gene-trap mutants show more severe abnormalities than another recently reported mouse line in which 7 contiguous genes including Gtf2ird1 are hemizygously deleted (28).…”
Section: Discussionmentioning
confidence: 76%
“…This dominantnegative explanation predicts that heterozygous mutants would have more severe consequences than a hemizygous Gtf2ird1 deletion. This does appear to be the case, as some of the gene-trap mutants show more severe abnormalities than another recently reported mouse line in which 7 contiguous genes including Gtf2ird1 are hemizygously deleted (28).…”
Section: Discussionmentioning
confidence: 76%
“…Additionally, certain do- mains of behavior, such as social interaction and empathy for others, are even enhanced in these patients (2-6, 31, 49). One strategy to unravel the complexity of WS is to use genetically altered mice that have defined alterations in one or more of these genes (16,50). To this end, we have previously generated LIMK1 Ϫ/Ϫ mice and shown that these mice are altered in learning and memory (14,25).…”
Section: Discussionmentioning
confidence: 99%
“…Although the most remarkable abnormalities in craniofacial development are observed for mice lacking the entire WBS syntenic region, 28 mice lacking the human proximal region spanning Trim50:Limk1 (that includes Baz1b) showed only very mild facial defects. On the contrary, no differences in cranial morphology were reported in mice lacking the human distal region (Limk1:Gtf2i), in contrast to reported cases of individuals with atypical deletions that postulate a role for the most WBSCR distal genes as involved in the craniofacial phenotype.…”
Section: Patient Wbs166mentioning
confidence: 99%